Locating de-lateralization in the pathway of sound changes affecting coda /l. Issue 1 (30th November 2020) - Strycharczuk, Patrycja; Derrick, Donald; Shaw, Jason
'Vocalization' is a label commonly used to describe an ongoing change in progress affecting coda /l/ in multiple accents of English. The label is directly linked to the loss of consonantal constriction observed in this process, but it also implicitly signals a specific type of change affecting manner of articulation from consonant to vowel, which involves loss of tongue lateralization, the defining property of lateral sounds. In this study, we consider two potential diachronic pathways of change: an abrupt loss of lateralization which follows from the loss of apical constriction, versus slower gradual loss of lateralization that tracks the articulatory changes to the dorsal component of /l/. We present articulatory data from seven speakers of New Zealand English, acquired using a combination of midsagittal and lateral EMA, as well as midsagittal ultrasound. Different stages of sound change are reconstructed through synchronic variation between light, dark, and vocalized /l/, induced by systematic manipulation of the segmental and morphosyntactic environment, and complemented by comparison of different individual articulatory strategies. Our data show a systematic reduction in lateralization that is conditioned by increasing degrees of /l/-darkening and /l/-vocalization. This observation supports the idea of a gradual diachronic shift and the following pathway of change: /l/-darkening, driven by the dorsal gesture, precipitates some loss of lateralization, which is followed by loss of the apical gesture. This pathway indicates that loss of lateralization is an integral component in the changes in manner of articulation of /l/ from consonantal to vocalic.